A lifetime with models, or toils and thrills of number crunching - Tsyganenko , Nikolai A. (Frontiers in Astronomy and Space Sciences, 2022)
Modeling the magnetosphere from satellite data has some analogy to the construction of identikit of a person from patchy information, collected by different people at different times under different lighting/viewing conditions. This article is a brief overview of the author's half-century-long efforts in building Earth's magnetosphere models, with some feats, setbacks, and lessons learned.